The Response to Oxidative DNA Damage in Neurons: Mechanisms and Disease. (31st January 2016) - Narciso, Laura; Parlanti, Eleonora; Racaniello, Mauro; Simonelli, Valeria; Cardinale, Alessio; Merlo, Daniela; Dogliotti, Eugenia
Abstract : There is a growing body of evidence indicating that the mechanisms that control genome stability are of key importance in the development and function of the nervous system. The major threat for neurons is oxidative DNA damage, which is repaired by the base excision repair (BER) pathway. Functional mutations of enzymes that are involved in the processing of single-strand breaks (SSB) that are generated during BER have been causally associated with syndromes that present important neurological alterations and cognitive decline. In this review, the plasticity of BER during neurogenesis and the importance of an efficient BER for correct brain function will be specifically addressed paying particular attention to the brain region and neuron-selectivity in SSB repair-associated neurological syndromes and age-related neurodegenerative diseases.